Morphological characterization and yield of pepper (Piper nigrum L.) types grown in Morogoro District, Tanzania - Abdul Jafari Shango; Ramadhani Omari Majubwa; Amon Petro Maerere (CABI Agriculture and Bioscience)
Abstract Background Pepper (Piper nigrum L.) is among key spice crops grown in Morogoro district of Tanzania. Most of the pepper types grown in the district are only known by their local names as Babu kubwa, Babu ndogo, Babu kati and Ismailia. This may limit information on germplasm collection or genetic resource for plant improvement and trade in markets with variety specifications. The aim of this study was to generate preliminary information of the pepper types based on their morphological characteristics for easy comparison with other known pepper varieties in the spices industry. Methods The evaluation of pepper morphological characters was conducted following a randomized complete block design with three replications and four treatments (pepper types). Observations were recorded with respect to 28 characters (9 qualitative and 19 quantitative) which entail vegetative (8) and reproductive (20) traits. The quantitative data for vegetative, inflorescence and berry characters were subjected to analysis of variance. Mean separation test was conducted using Turkey’s Honest Significance Test at (α = 0.05). Correlation and regression analyses were performed to explore the relationship between yield and yield attributes of pepper. Results Babu kubwa and Babu ndogo pepper types were characterized by erect and horizontal branching habit, whereas the others showed hanging habit. Babu kubwa had longer spikes (12.4 cm), leaves blade (17.9 cm), leaf petiole (2.8 cm), wider leaves (12.9 cm) and larger berries (5.8 mm) than all other pepper types. Babu kubwa and Babu kati had cordate and acute leaf bases, respectively while other types had round leaf base shapes. The highest number of flowers was recorded on Babu kubwa (93.5) and Ismailia (90.7) with spikes weighing 7.6 g and 7.5 g, respectively compared to other types. Babu ndogo and Ismailia had compact spikes, while other types had medium loose spikes. Babu kati had the highest number of spikes kg−1 (282.6) due its lower spike weight compared to other types. The highest weight of 100 fresh spikes (704.3 g) and 1000 fresh berries (164.2 g) was recorded on Ismailia. Spike length was significantly positively correlated to yield (r = 0.23, R2 = 0.08, p < 0.001). However, yield had a significant negative correlation with the number of spikes kg−1 (r =  −0.85, R2 = 0.017, p = 0.001) and fresh weight of 1000 berries (r = −0.91, R2 = 0.003, p = 0.04). Conclusions The pepper types grown in Morogoro district differed significantly based on most of the evaluated traits. This information can be used to formulate methods and strategies for conservation and in turn genetic improvement of the crop. Despite that the pepper types literary matched with characters of some well-known commercial varieties, confirmation of genetic relatedness is yet needed. Further studies need to be conducted in consecutive years and involve assessment of internal quality attributes. Other studies should encompass wider range of pepper types from other producing areas in Tanzania in order to establish their morphological distinctness, genetic diversity and interrelationships in relation to the globally known commercial varieties.